Adjunct Fenofibrate Up‐regulates Bile Acid Glucuronidation and Improves Treatment Response For Patients With Cholestasis. Issue 12 (27th August 2021) - Gallucci, Gina M.; Trottier, Jocelyn; Hemme, Christopher; Assis, David N.; Boyer, James L.; Barbier, Olivier; Ghonem, Nisanne S.
Abstract : Accumulation of cytotoxic bile acids (BAs) during cholestasis can result in liver failure. Glucuronidation, a phase II metabolism pathway responsible for BA detoxification, is regulated by peroxisome proliferator–activated receptor alpha (PPARα). This study investigates the efficacy of adjunct fenofibrate therapy to up‐regulate BA‐glucuronidation and reduce serum BA toxicity during cholestasis. Adult patients with primary biliary cholangitis (PBC, n = 32) and primary sclerosing cholangitis (PSC, n = 23), who experienced an incomplete response while receiving ursodiol monotherapy (13‐15 mg/kg/day), defined as serum alkaline phosphatase (ALP) ≥ 1.5 times the upper limit of normal, received additional fenofibrate (145‐160 mg/day) as standard of care. Serum BA and BA‐glucuronide concentrations were measured by liquid chromatography–mass spectrometry. Combination therapy with fenofibrate significantly decreased elevated serum ALP (−76%, P  < 0.001), aspartate transaminase, alanine aminotransferase, bilirubin, total serum BAs (−54%), and increased serum BA‐glucuronides (+2.1‐fold, P  < 0.01) versus ursodiol monotherapy. The major serum BA‐glucuronides that were favorably altered following adjunct fenofibrate include hyodeoxycholic acid–6G (+3.7‐fold, P  < 0.01), hyocholic acid–6G (+2.6‐fold, P  < 0.05), chenodeoxycholic acid (CDCA)–3G (−36%), and lithocholic acid (LCA)–3G (−42%) versus ursodiol monotherapy. Fenofibrate also up‐regulated the expression of uridine 5′‐diphospho‐glucuronosyltransferases and multidrug resistance–associated protein 3 messenger RNA in primary human hepatocytes. Pearson's correlation coefficients identified strong associations between serum ALP and metabolic ratios of CDCA‐3G (r 2  = 0.62, P  < 0.0001), deoxycholic acid (DCA)‐3G (r 2  = 0.48, P  < 0.0001), and LCA‐3G (r 2  = 0.40, P  < 0.001), in ursodiol monotherapy versus control. Receiver operating characteristic analysis identified serum BA‐glucuronides as measures of response to therapy. Conclusion: Fenofibrate favorably alters major serum BA‐glucuronides, which correlate with reduced serum ALP levels and improved outcomes. A PPARα‐mediated anti‐cholestatic mechanism is involved in detoxifying serum BAs in patients with PBC and PSC who have an incomplete response on ursodiol monotherapy and receive adjunct fenofibrate. Serum BA‐glucuronides may serve as a noninvasive measure of treatment response in PBC and PSC. Abstract : Combination therapy with fenofibrate favorably alters BA‐glucuronidation as a PPARa‐mediated mechanism to reduce elevated serum BAs in patients with PBC and PSC who are incomplete responders to Ursodiol monotherapy. This study also identifies serum BA‐glucuronides and their respective metabolic ratios as indicators of response to therapy. Serum BA‐glucuronides may serve as mechanistically relevant secondary endpoints in clinical trials for PBC and PSC with anti‐cholestatic agents.image